Hubungan antara Pengetahuan dan Sikap dengan Perilaku Masyarakat dalam Pencegahan Penyakit Diabetes Mellitus di Desa Sukagumiwang (Studi Kasus pada Masyarakat Berusia 45-54 Tahun) - Priyatna, Bayu Sela; Wahyudin, Wahyudin; Widiyasari, Widiyasari (Jurnal Kesehatan Holistic, 2025)
Introduction: Diabetes Mellitus (DM) is a chronic metabolic disease characterized by elevated blood sugar levels. In essence, behavior is a human activity to respond to stimuli in the environment, including responses to health knowledge and attitudes possessed. The results of Riskesdas 2018 prevalence of DM in Indonesia amounted to 2%, an increase compared to the results of Riskesdas 2013 of 1,5%. As for DM sufferers in Indramayu Regency in 2021 there were 11.341 people in 2022 it increased to 17.868 people. From this data, in 2022 the Sukagumiwang Health Center ranks first in the highest number of DM sufferers, which is 2.612 people. This study aims to determine the relationship between knowledge and attitudes with community behavior in preventing diabetes mellitus in Sukagumiwang Village Method: This research method uses quantitative analytical study methods with a cross-sectional approach. The population in this study was 1.219 people and the research sample was 301 respondents. The instrument used in this study was a questionnaire. The design of univariate analysis and bivariate analysis was performed with the chi-square test. Results: The results of this study found that the variable that was statistically meaningful to DM prevention behavior was the knowledge variable (p=0,020), and the variable that was not related to DM prevention behavior was the attitude variable (p=0,384). Conclusion: This study concludes that the better the knowledge or attitude of the community, the better it is in preventing DM. The suggestion in this study is that the public is expected to increase knowledge about DM disease by seeking information from various sources, so that they can apply DM prevention behaviors.